Unsteady boundary layer flow of a micropolar fluid near the rear stagnation point of a plane surface - Lok, Yian Yian; Amin, Norsarahaida; Pop, Ioan (Elsevier SAS, 2003)
The growth of the boundary layer flow of a viscous and incompressible micropolar fluid started impulsively from rest near the rear stagnation point of a two-dimensional plane surface is studied theoretically. The transformed non-similar boundary-layer equations are solved numerically using a very efficient finite-difference method known as Keller-box method. This method may present well-behaved solutions for the transient (small time) solution up to the separation boundary layer flow. Numerical results are given for the reduced velocity and microrotation profiles, as well as for the skin friction coefficient when the material parameter K takes the values K=0 (Newtonian fluid), 0.5, 1, 1.1, 1.5, 2, 2.5 and 3 with the boundary condition for microrotation n=0 (strong concentration of microelements) and n=1/2 (weak concentration of microelements), respectively. Important features of these flow characteristics are shown on graphs and in tables